Determinants of employee eco-initiatives in Indian hotel industry. (2019) - Tom, Mercy; Soumyaja, Devi
Results of a questionnaire survey completed by 402 respondents who were all employees of hotels that have adopted eco-friendly practices showed that eco-initiatives are significantly and positively correlated to conservatism, commitment to the cause of the environment, and monetary rewards and recognition; significantly and negatively correlated to self-transcendence and environmental training; and bear no significant relationship with environmental communication and self-enhancement. Future research should consider the role of guests in promoting employee eco-initiatives.